Peran Day Care Dalam Stimulasi Perkembangan Fisik Motorik Anak Usia Dini Di Buncha Daycare Jakarta Pusat - Nurpadilah, Nurpadilah; Choiriyah, Choiriyah; Apriyansyah, Chandra (CV. ITTC INDONESIA, 2024)
Nurpadilah, The Role of Day Care in Stimulating Early Childhood Physical Motor Development at Buncha Daycare, Central Jakarta (2024). Thesis. Jakarta: College of Teacher Training and Education Panca Sakti Bekasi. 2024. This study aims to examine the role of day care in stimulating the physical motor development of early childhood in buncha day care central Jakarta, using physical motor development instruments with the role of day care in child growth and development and the effectiveness of day care in stimulating children's physical motor development using the Likert model attitude scale form. The research method used is descriptive research method with qualitative approach. The subjects of this study were elements of the day care institution which included the principal, educators/caregivers, and parents at Buncha Day care. Data collection techniques using interviews, observation and documentation with a qualitative data analysis process through several activities, namely data reduction, data display and conclusion drawing/verification. The results showed that the growth and development of children (aged 2-3 years) there are still those who are not actively participating in activities (rare entry / new to daycare) and must be considered again by employees or parents and more routine child stimulation is needed because seeing growth and development is not in accordance with the age stage. Through analysis of the results of observations, what should be considered